Massimo il Greco e gli ordini religiosi dell'Occidente Esperienza ed evidenza documentaria nella testimonianza alla Moscovia cinquecentesca - Romoli, Francesca (Europe in between. Histories, cultures and languages from Central Europe to the Eurasian Steppes, 2021)
Maximus the Greek (c.1470-1556), born Michael Trivolis, is a complex figure. As a copyist and Dominican novice, Orthodox monk and humanist, he stands at the crossroads of different worlds, cultures and creeds. His life path unwound between his besieged homeland, humanist Italy - in the Republics of Florence and Venice and in the Papal States - Mount Athos and the Moscow of Vasili III and Ivan IV. This path brought him exceptionally into contact with both Latin and vernacular humanism and Latin Christianity, with the Greek and Slavic Byzantine tradition, with Orthodoxy and Islam, in a cultural, linguistic and religious polyphony that is at once his hallmark and the key to his literary legacy. The subject of this book is Maximus the Greek's testimony regarding the Western religious orders contained in the Terrible and Memorable Narration, and the Perfect Form of Monastic Life and the Letter on the Franciscans and the Dominicans. The comparison with documentary evidence, made here for the first time, demonstrates the reliability of these works, casting light on the author's life and the sources, places and people involved in it.